"Mom, they are going to kill my dad!": a personal narrative on capital punishment from a convict criminology perspective - Williams, D. J. (Critical criminology, 2014)
Capital punishment, although opposed by numerous scholars and banned in several countries, continues to be practiced in many locations under a popular rationale associated with retributive justice. While there has been extensive debate on this issue for decades among scholars, policymakers, correctional professionals, and the media; other important voices, specifically the voices of family members of executed convicts, have been ignored or discounted. Situated within a convict criminology perspective, this paper focuses on a personal narrative of how the issue of capital punishment was experienced by the partner (second author of this paper) of an executed convict. This narrative powerfully illustrates complexities and unintended social injustices toward family members that can occur from capital punishment.